Study of Role of Financial Institution in Financial Inclusion - Ishan Khatri; Prarthana Fabyani; Chehak Rajgarhia; Sejal Murarka (International Journal of Engineering and Management Research, 2020)
India is one of the largest growing economies in the world. Financial inclusion is providing financial services at an affordable rate to all people. It comes into existence in the year 1950 establishment of Reserve Bank of India. There are various incentives which have been undertaken to increase financial inclusion in India. With the nationalization of commercial banks. And the formation of NABARD Self-help Groups and Kisan credit bank. After 2000, the schemes like Swavalamban swabhiman have been launched to increase its role. The schemes by government of India like PMJDY and Startup India schemes. Financial inclusion helps in forming cashless economy and increase capital formation and increase economic growth of the country. It provides business and growth opportunities to the Intermediaries. This system also provides affordable services to the poor and played a vital role in improving country financial services.